Cerebral babesiosis caused by Babesia bovis (Babés 1888 Starcovici 1893) in calves, in the state of Mato Grosso do Sul - Kessler, Raul Henrique; Madruga, Cláudio Roberto; Schenk, Maria Aparecida M.; Ribeiro, Olímpio Crisóstomo (Pesquisa Agropecuaria Brasileira, 2014)
Three cases of death caused by Babesia bovis, One in a 13-day-old Nelore x Fleckvieh female calf, one in a 25-day-old Ibagé male calf and one in a 108-day-old Nelore male calf are described. All were acute cases without the possibility of an in vivo diagnosis or treatment. The diagnosis was based on necropsy, microscopic examination of twain, kidney and heart preparations stained by May-Grünwald-Giemsa and histopathology examination of the various, internal organs stained by Haematoxylin-Eosin. The specific in diagnosis was based on the morphology of the organisms and the characteristical localization of parasitized erythrocytes in the blood capillaries of the internal organs. This is the first notification of the occurrence of clinical cases of babesiosis by S. bovis in Mato Grosso do Sul, Brazil.